Tungsten fiber reinforced tungsten (Wf/W) using yarn based textile preforms. (19th November 2021) - Coenen, J W; Huber, P; Lau, A; Raumann, L; Schwalenberg, D; Mao, Y; Riesch, J; Terra, A; Linsmeier, Ch; Neu, R
Abstract: Material related limitations are one of the main challenges for the design of future fusion reactors. Tungsten (W) as the primary material choice is considered resilient against erosion, has the highest melting point of any metal and shows low activation after neutron irradiation. However, W is intrinsically brittle and faces operational embrittlement. To overcome these issues, W-based composites have been in development. W fiber-reinforced W composite materials (W f /W) incorporate extrinsic toughening mechanisms allowing the redistribution of stress peaks and thus overcoming the intrinsic brittleness problem. In this contribution recent results on the incorporation of new textile preformes into W f /W production will be given with a focus on the production via chemical vapor deposition of tungsten-based materials. The use of tungsten yarns, instead of single wires for the textile production is elaborated.